Al-Din al-Fit’rat’ Versus ‘Religion of Nature or Naturalism’: The Misunderstood Terms Regarding True Spirit of Islam (Al-Qamar, 2023)
The two terms ‘al-Fitrat’ and ‘Nature’ have always been used as synonyms. Books and internet sources including encyclopaedias, provide abundant information based on the concept as these two terms as synonyms.  But this paper will reveal that it is a mistake to regard them synonyms. When we expend this concept to Islam as Al-Din Al Fitrat and Western theory of Naturalism and Natural Religions, these terms become ambiguous or having different meanings. Situation becomes more grave when we use the term Nature about something as having some latent and permanent rules, inaccordance with the such thing is bound to work blindly such as the  nature of wild animals e.g.snakes, the scorpion, the lion or the fierce phenomenon e.g. the natural forces.Application of the term ‘nature’ and use of the term ‘naturalism’ in comparison to Islamic concept of ‘Al-fitrat’is distorting image of Islam as Din al Fitrat.  Western concept of ‘Nature’ and ‘Naturalism’ and ‘Natural explanation’, of the Universe are contrary to the concept of Al-Fitrat. The former is cruel, deterministic, and bound force to act according to its own deterministic rules and to act likewise towards other existents. But Islamic concept of ‘al Fitrat’, is neither deterministic nor static. It is creative and kind, that is why God calls himself Al Raheem, al Rehman, and claims that Islam as ‘Din Al- Fitrat’ as well as everyone is born on the basis of ‘al din al fitrat’. So the ‘Nature’ or ‘Naturalism’ does not qualify to be regarded as equal to ‘al-fitrat’.
Keywords: Al-Fitrat; Creationism; Free Will and Determinism; Muslim Theology; Nature; Naturalism; evealed and Natural Religions; Totemism